Classification of occupations - Uter, Wolfgang (Kanerva's Occupational Dermatology, 2019)
For the epidemiology of work-related skin diseases, comprising surveillance and analytical approaches, occupational exposure can be represented by the occupation (job title) or the industry a person is working in. For both concepts, several international and national classification systems exist, which are revised from time to time. As global classification of occupations, the “International Standard Classification of Occupations” (ISCO, presently ISCO-08) of the International Labour Organisation is available. The “International Standard Industrial Classification of all Economic Activities” (ISIC), presently in its fourth revision, issued by the United Nations Statistics Division, is globally used to document industrial sectors; however, in several countries national classification systems are (also) used. All such classifications have been developed to serve broad administrative and research purposes. For this reason, it is often necessary to adapt a classification of occupation or industry to medical needs. To this end, a more refined subcategorization, respecting, however, the hierarchical structure of the classification it is based upon, and general rules for the construction of classification systems, can be employed to achieve a best possible degree of detail. Conversely, some other categories (e.g., different types of “office work”) deemed largely identical with regard to relevant exposures may be aggregated. The aim is to achieve a clinically manageable, reliable catalogue and consistent usage aided by clear definitions.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Classification; Epidemiology; Exposure; ILO; Industry; ISCO; ISIC; Job exposure matrix; NACE; NAICS; Occupation; Surveillance